PENERAPAN PERATURAN DAERAH KABUPATEN INDRAMAYU NOMOR 8 TAHUN 2015 DI MA’HAD AL-ZAYTUN - Abdur Rahim; Saepul Aziz Al-Haq; Sudrajat Fahri; Fathur Ahsanu; Supriyatno Supriyatno; Yudi Prasetyo; Zamroni Zamroni; Partono Partono (LPPM Universitas Bina Bangsa, 2024)
Education become a medium for developing the potential and educating students. It is from education that character is formed, so character education is the main key to building nationalism in the midst of the era of globalization that is sweeping the world. So the application of character education has the functions of building students to be better and of course in accordance with applicable regulations. So in this community service activity carried out in the Madrasah Aliyah Ma'had Al-Zaytun environment, by providing material on the application of Indramayu district regional regulations number 8 of 2015, it can provide a broad understanding of the importance of character education. The presentation of material by using the method of providing input followed by questions and answers. The results of observations that have been carried out in depth show that the personal character of Ma'had Al-Zaytun students is in accordance with Indramayu district regional regulations number 8 of 2015